2015
DOI: 10.1071/9781486300679
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Evolution of Crocodylians

Abstract: Biology and Evolution of Crocodylians is a comprehensive review of current knowledge about the world's largest and most famous living reptiles. Gordon Grigg's authoritative and accessible text and David Kirshner's stunning interpretive artwork and colour photographs combine expertly in this contemporary celebration of crocodiles, alligators, caimans and gharials. This book showcases the skills and capabilities that allow crocodylians to live how and where they do. It covers the biology and ecology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
329
0
23

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(356 citation statements)
references
References 0 publications
4
329
0
23
Order By: Relevance
“…This widespread turnover involving redistribution suggests easy dispersal across large portions of the whole of Pangea. It may be tempting to assume that the broad distribution of the group is the result of marine adaptations of some kind as observed in some extant crocodylians47484950. Saltwater tolerance, an extreme marine adaptation, is the result of soft-tissue adaptations including the combination of extremely low skin permeability, the presence of lingual salt glands, and special functions of the kidneys and cloaca47, which would be difficult to infer for most fossils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This widespread turnover involving redistribution suggests easy dispersal across large portions of the whole of Pangea. It may be tempting to assume that the broad distribution of the group is the result of marine adaptations of some kind as observed in some extant crocodylians47484950. Saltwater tolerance, an extreme marine adaptation, is the result of soft-tissue adaptations including the combination of extremely low skin permeability, the presence of lingual salt glands, and special functions of the kidneys and cloaca47, which would be difficult to infer for most fossils.…”
Section: Discussionmentioning
confidence: 99%
“…It may be tempting to assume that the broad distribution of the group is the result of marine adaptations of some kind as observed in some extant crocodylians47484950. Saltwater tolerance, an extreme marine adaptation, is the result of soft-tissue adaptations including the combination of extremely low skin permeability, the presence of lingual salt glands, and special functions of the kidneys and cloaca47, which would be difficult to infer for most fossils. Saltwater tolerance or even possible marine adaptations were hypothesized previously for the phytosaur Mystriosuchus from the Upper Triassic of Europe based on both morphological and depositional data646515253.…”
Section: Discussionmentioning
confidence: 99%
“…Alligatoroid species were not included in the sample because the current study specifically focuses on piscivorous specialization. Crocodylus is the most diverse and species‐rich genus in extant crocodylians, including 12 known species (Grigg & Kirshner, ) from blunt‐snouted type to slender‐snouted type. A recent molecular study by Oaks () revealed the late Miocene divergence of this group, suggesting that Crocodylus snout shape is ecologically plastic and is not strongly constrained by the phylogenetic relationships.…”
Section: Methodsmentioning
confidence: 99%
“…Many features commonly associated with birds, such as feathers, the furcula (wishbone), and a specialized wrist joint, were already present in small predatory dinosaurs. Presentday crocodylians are represented only by some 25 species, which are mostly amphibious ambush predators (Grigg and Kirshner, 2015; Figure 9). The major diversification of birds, during which most major modern groups evolved, took place only during the Cenozoic (Mayr, 2014).…”
Section: Reptiliamentioning
confidence: 99%